Pelatihan Pencatatan Laporan Keuangan untuk Meningkatkan Transparansi Keuangan Pondok Pesantren Nurul Jadid - Azizatul Fitriyah; Fakhri Siddiqi (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Training activities on financial statement recording in Islamic boarding schools are one form of implementation of Field Work Practice (PKL) aimed at assisting pesantren institutions in preparing accurate, transparent, and accountable financial reports. This activity was conducted at BUMPES Nurul Jadid as a pesantren business unit engaged in the economic activities of the santri community. In this program, students played an active role in providing technical assistance for daily transaction recording, cash report preparation, and helping to compile simple financial statements based on basic accounting principles. The results of the study indicate that orderly and systematic financial recording helps pesantren managers control cash flow, prepare accountable financial reports, and increase stakeholder trust. Therefore, improving the financial recording system is an essential requirement for realizing professional and sustainable pesantren governance.